THE CONCEPTUAL FOUNDATION OF HARMONIZATION OF DIMENSIONAL DESIGN SOLUTION WHILE PLANNING AND WORKING OUT OF COAL-GAS DEPOSITS BY UNDERGROUND METHODS - MEDYANYK, Volodymyr; MALASHKEVYCH, Dmytro; POCHEPOV, Victor; MAMAIKIN, Oleksandr; LAPKO, Victor (My University, 2018)
Following the 25th World Mining Congress in Astana, it is concluded how important the coal mining industry nowadays. There are only a few energy sources that can produce heat and electricity day-and-night. Each source of energy has its own pros and cons. Ukraine, like any other country, faces difficulties using nuclear power. There are several major players in the oil and gas market.
Keywords: underground mining; design; planning; engineering solutions; innovations